Utilization of Psychotropic Medications and Polypharmacy Among Adults in Jazan Region, Saudi Arabia - Abdulkarim M. Meraya; Monira Alwhaibi; Mamoon H Syed; Ali Shwihi; Muath Mashraqi; Rina Tripathi; Yasser Buayti; Dhaifallah Moraya (Indonesian Journal of Pharmacy, 2020)
Globally, there has been a surge in the prevalence of mental health disorders, not excluding Saudi Arabia. The availability of newer psychotropic medications has led to increased prescribing and polypharmacy. In Saudi Arabia, exploration of the knowledge gap between the outpatient use of psychotropic medications and the extent of polypharmacy has been scarce in the literature. This study evaluated the prescription pattern of psychotropic medications and the prevalence of psychotropic polypharmacy among adult patients with behavioral/mental illnesses. The study was conducted in the psychiatric outpatient clinics of five hospitals in Jazan Region of Saudi Arabia. A retrospective cross-sectional study was conducted with a non-random sample of adults with behavioral/mental illnesses. Psychotropic polypharmacy was the presence of ≥2 psychotropic medication prescriptions. We conducted multivariable logistic regression models to examine the factors associated with psychotropic polypharmacy. A total of 3.052 adults with a behavioral/mental illness were included in the study. Of these, 74.6% had antidepressant prescriptions. The second most prescribed drug class was antipsychotics (51.9%). Furthermore, 65.3% had psychotropic polypharmacy, and 48.2% had interclass psychotropic polypharmacy. Adults with anxiety and other mood disorders were less likely to engage in psychotropic polypharmacy and interclass polypharmacy use than those with depression. However, adults with schizophrenia (adjusted odds ratio [AOR]: 1.91; p<0.001) were more likely to engage in interclass polypharmacy use than those with depression. Adults with behavioral/mental illnesses in Jazan Region of Saudi Arabia have high rates of antidepressants and antipsychotics use. Additionally, psychotropic polypharmacy is a common prescribing practice, and further evaluation of the safety profile of these combinations is warranted.